Clinical implications for substandard, nonproprietary medicines in multiple sclerosis: focus on fingolimod - Correale J; Chiquete E; Boyko A; Beran RG; Strauch JB; Milojevic S; Frider N (Dove Medical Press, 2016)
Jorge Correale,1 Erwin Chiquete,2 Alexey Boyko,3 Roy G Beran,4–6 Jorge Barahona Strauch,7,8 Snezana Milojevic,9 Nadina Frider101Department of Neurology, Raúl Carrea Institute for Neurological Research, Foundation for the Fight against Infant Neurological Illnesses (FLENI), Buenos Aires, Argentina; 2Department of Neurology and Psychiatry, Salvador Zubirán National Institute of Medical Sciences and Nutrition, Mexico City, Mexico; 3Clinical and Research Center “MS and Other Demyelinating Diseases” at the Neuroclinical Hospital, Department of Neurology, Neurosurgery and Medical Genetics of the Pirogov Russian National Research Medical University, Moscow, Russia; 4South Western Clinical School, University of New South Wales, Liverpool, 5Department of Neurology, Liverpool Hospital, Sydney, NSW, 6School of Medicine, Griffith University, Southport, QLD, Australia; 7Department of Neurology, Clínica Alemana de Santiago, 8School of Medicine, Universidad del Desarrollo, Santiago, Chile; 9Novartis Pharma AG, Basel, Switzerland; 10Novartis Latin America and Canada Region, Buenos Aires, ArgentinaAbstract: Both proprietary and nonproprietary medicines are expected to undergo rigorous preapproval testing and both should meet stringent health authority regulatory requirements related to quality to obtain approval. Nonproprietary (also known as copy, or generic) medicines, which base their authorization and use on the proprietary documentation and label, are often viewed as a means to help lower the cost and, thus, increase patient access. If these medicines fail to meet quality standards, such as good manufacturing practice and bioequivalence (in humans), they are then defined as substandard copies and can pose serious risks to patients in terms of safety and efficacy. Potentially noncontrolled or different manufacturing process and excipients in nonproprietary medicines may result in poor batch-to-batch reproducibility (accurate and consistent quantity of each ingredient in each capsule/tablet) and lower quality. Substandard, nonproprietary copies of medicines that are immunomodulatory or immunosuppressive are of concern to patients due to their possible untoward safety and lack of efficacy events. This article reviews the potential risks associated with nonproprietary medicines that do not meet the regulatory requirements of the United States Food and Drug Administration, the European Medicines Agency, or the World Health Organization. The clinical implications for patients are described. This article focuses on nonproprietary medicines for multiple sclerosis, particularly fingolimod, that are not identical to proprietary versions and could thus fail to meet efficacy expectations or have different impact on the safety of patients with multiple sclerosis.Keywords: bioequivalence, fingolimod, multiple sclerosis, proprietary, substandard copies, toxicity